A Hidden Culture of Coping: Insights on African American Women's Existence in Predominately White Institutions. (2nd January 2019) - Apugo, Danielle
Abstract : Limited scholarship has examined the relationship between pervasive intellectual, cultural, and racial stereotypes and their role in establishing and perpetuating psychological anguish. This effect can potentially hinder the academic success and use of healthy coping mechanisms among African American women students. Using Black feminist thought (BFT) as an analytic lens, this article examines some of the barriers related to the existence of African American women at predominately White institutions (PWIs).